Faktor-Faktor yang Berhubungan dengan Kejadian BBLR di RS Kristen Lende Moripa Sumba Barat - Erfina Intania Jaha; Utma Aspatria; Marselinus Laga Nur (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Low birth weight (LBW) is a baby born with a birth weight of less than 2500 grams, regardless of gestational age or gestational age. This study aims to determine the factors associated with the incidence of low birth weight LBW at the Lende Moripa Kriten Hospital, West Sumba. The type of research is analytical survey research with a case control design using a retrospective approach. The population in this research was all 814 mothers who gave birth to live babies in the period January – December 2023 at Lende Moripa Christian Hospital, West Sumba and the sample was 86 mothers. Data were analyzed using univariate analysis and bivariate analysis using the chi-square statistical test. The results of the study showed that there was a significant relationship between history of antenatal care (ρ value = 0.031), history of TTD consumption (ρ value = 0.030), history of maternal illness (ρ value = 0.048), and the incidence of LBW. Based on the research results, it shows that there is a relationship between the variables history of ANC, history of TTD consumption, history of maternal illness, and the incidence of LBW at Lende Moripa Christian Hospital, West Sumba. This research can be used as a consideration in making policies in hospitals, and continuing to improve preventive and promotive efforts for the community, especially pregnant women and families, by utilizing existing media in the digital era such as mass media and electronic media.